2013
DOI: 10.1136/acupmed-2013-010394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupuncture on the Symptoms of Anxiety and Depression Caused by Premenstrual Dysphoric Disorder

Abstract: Objective The objective of this investigation was to evaluate the effects of acupuncture and sham acupuncture on the symptoms of anxiety and depression brought on by premenstrual dysphoric disorder (PMDD). Methods In a single-blind randomised clinical trial, 30 volunteers with PMDD were assigned alternately to group 1 (acupuncture) or group 2 (sham acupuncture), and completed an evaluation of symptoms of anxiety and depression using the Hamilton Anxiety (HAM-A) and Hamilton Depression (HAM-D) Rating Scales. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
2
8
0
1
Order By: Relevance
“…Our finding that EA appeared to be better at improving sleep disturbance (a somatic symptom) is partly consistent with previous studies demonstrating the beneficial effect of EA on depressive symptoms,25 26 in which EA (alone or in combination) resulted in relatively lower sleep disturbance scores compared to CBT. Previous research has suggested that acupuncture may help regulate circadian rhythm and melatonin levels, which are reported to be intimately linked to sleep-related problems and depressive disorders 27–30…”
Section: Discussionsupporting
confidence: 92%
“…Our finding that EA appeared to be better at improving sleep disturbance (a somatic symptom) is partly consistent with previous studies demonstrating the beneficial effect of EA on depressive symptoms,25 26 in which EA (alone or in combination) resulted in relatively lower sleep disturbance scores compared to CBT. Previous research has suggested that acupuncture may help regulate circadian rhythm and melatonin levels, which are reported to be intimately linked to sleep-related problems and depressive disorders 27–30…”
Section: Discussionsupporting
confidence: 92%
“…74 Except for the meta-analyses by Linde and colleagues, 65,66 only individual RCTs have been reported in the scientific literature with variable sham response rates on disorders, such as irritable bowel syndrome, 75 premenstrual syndrome, 76 and post-chemotherapy chronic fatigue. 77 This predominant efficacy in somatoform disorders is not surprising, in view of the strong action of acupuncture on peripheral autonomic functions.…”
Section: Placebo Responders In Non-pharmacological Trialsmentioning
confidence: 99%
“…Present study just revealed that the SAS and Kupperman score of patients were lowered after three months' treatment. This might be explained by the mind adjustment and mental improving effects of acupuncture [28, 29]. …”
Section: Discussionmentioning
confidence: 99%